A lysozyme-like protein in Brucella abortus is involved in the early stages of intracellular replication - del Giudice, Mariela Giselda (2013)
Secretion of proteins in Gram-negative bacteria is a high-energy consuming process that requires the translocation across two membranes and a periplasmic space composed of a mesh like layer, the peptidoglycan. To achieve this, bacteria have evolved complex secretion systems that cross these barriers and, in many cases, there are specific peptidoglycanases that degrade the peptidoglycan to allow the proper assembly of the secretion machinery. We describe here the identification and characterization of a muramidase in Brucella abortus that participates in the intracellular multiplication in professional and non-professional phagocytes. We demonstrated that this protein has peptidoglycanase activity, that a strain with a clean deletion of the gene displayed a defect in the early stages of the intracellular multiplication curve and that this is dependent on the lytic activity. While neither the attachment nor the invasion of the strain was affected we demonstrated that it had a defect in excluding the lysosomal marker LAMP-1 but not in acquiring the reticulum endoplasmic marker calnexin, indicating that the gene participates in the early stages of the intracellular trafficking but not in the establishment of the replicative niche. Analysis of the assembly status and functionality of the VirB secretion apparatus indicated that the mutant has affected the proper function of this central virulence factor.